2017 IEEE 56th Annual Conference on Decision and Control (CDC) 2017
DOI: 10.1109/cdc.2017.8264040
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain forecasting approach for latency reduction in direct human-computer interaction

Abstract: Abstract-The problem of latency reduction in direct humancomputer interaction is considered and formulated as a trajectory prediction problem. To solve the problem, the predictor is constructed as a frequency-domain approximation of the noncasual ideal predictor. This approximation can be computed analytically, or obtained as an optimization task. An adaptive modification of the forecasting algorithm is proposed taking into account possible variations in user behavior. Experimental results illustrate the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Experimental results illustrate the applicability of the proposed forecasting algorithm and its performance compared to other methods. Preliminary results of this study were reported in Aranovskiy et al (2017b). Extending that work, this manuscript contains i) the proof of the forecasting accuracy bound (15), see Proposition 1, ii) the detailed description of the experimental setup and iii) comparison to the methods currently available in patents Moussavi (2014) and Qingkui (2014).…”
Section: Introductionmentioning
confidence: 80%
“…Experimental results illustrate the applicability of the proposed forecasting algorithm and its performance compared to other methods. Preliminary results of this study were reported in Aranovskiy et al (2017b). Extending that work, this manuscript contains i) the proof of the forecasting accuracy bound (15), see Proposition 1, ii) the detailed description of the experimental setup and iii) comparison to the methods currently available in patents Moussavi (2014) and Qingkui (2014).…”
Section: Introductionmentioning
confidence: 80%
“…Another approach based on finite impulse response (FIR) filters has been proposed recently in [2]. It demonstrates good robustness properties with respect to measurement noise, but still requires more computational capacities (involves matrix manipulations with 16 times 16 matrices for both X and Y) without a corresponding quality of differentiation improvement comparing to HOM differentiator.…”
Section: Time Derivative Estimation Techniquesmentioning
confidence: 99%
“…The calculations that follow are described for the x coordinate only for simplicity, and must be performed for y as well in real use 2. Our prediction algorithm and tuning process are available at ns.inria.fr/loki/TTp/.…”
mentioning
confidence: 99%